Question
upstudy study bank question image url

Solve for \( u \). \( \frac{-11 u}{u^{2}-u-30}-\frac{8}{u-6}=\frac{u}{u+5} \) If there is more than one solution, separate them with commas. If there is no solution, click on "No solution".

Ask by Franklin Weaver. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( u = -8 \)

Solution

Solve the equation \( \frac{-11u}{u^{2}-u-30}-\frac{8}{u-6}=\frac{u}{u+5} \). Solve the equation by following steps: - step0: Solve for \(u\): \(\frac{-11u}{u^{2}-u-30}-\frac{8}{u-6}=\frac{u}{u+5}\) - step1: Find the domain: \(\frac{-11u}{u^{2}-u-30}-\frac{8}{u-6}=\frac{u}{u+5},u \in \left(-\infty,-5\right)\cup \left(-5,6\right)\cup \left(6,+\infty\right)\) - step2: Rewrite the fraction: \(-\frac{11u}{u^{2}-u-30}-\frac{8}{u-6}=\frac{u}{u+5}\) - step3: Multiply both sides of the equation by LCD: \(\left(-\frac{11u}{u^{2}-u-30}-\frac{8}{u-6}\right)\left(u+5\right)\left(u-6\right)=\frac{u}{u+5}\times \left(u+5\right)\left(u-6\right)\) - step4: Simplify the equation: \(-19u-40=u^{2}-6u\) - step5: Move the expression to the left side: \(-19u-40-\left(u^{2}-6u\right)=0\) - step6: Subtract the terms: \(-13u-40-u^{2}=0\) - step7: Factor the expression: \(-\left(5+u\right)\left(8+u\right)=0\) - step8: Divide the terms: \(\left(5+u\right)\left(8+u\right)=0\) - step9: Separate into possible cases: \(\begin{align}&5+u=0\\&8+u=0\end{align}\) - step10: Solve the equation: \(\begin{align}&u=-5\\&u=-8\end{align}\) - step11: Check if the solution is in the defined range: \(\begin{align}&u=-5\\&u=-8\end{align},u \in \left(-\infty,-5\right)\cup \left(-5,6\right)\cup \left(6,+\infty\right)\) - step12: Find the intersection: \(u=-8\) The solution to the equation \( \frac{-11u}{u^{2}-u-30}-\frac{8}{u-6}=\frac{u}{u+5} \) is \( u = -8 \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To solve the equation \[ \frac{-11 u}{u^{2}-u-30}-\frac{8}{u-6}=\frac{u}{u+5}, \] we start by factoring the quadratic \(u^{2}-u-30\). This can be factored as \((u-6)(u+5)\). Now, substitute this back into the equation: \[ \frac{-11 u}{(u-6)(u+5)}-\frac{8}{u-6}=\frac{u}{u+5}. \] Next, find a common denominator for all terms. The common denominator is \((u-6)(u+5)\). Rewriting each term gives: \[ \frac{-11u}{(u-6)(u+5)} - \frac{8(u+5)}{(u-6)(u+5)} = \frac{u(u-6)}{(u-6)(u+5)}. \] Now combine the left side: \[ \frac{-11u - 8(u+5)}{(u-6)(u+5)} = \frac{u(u-6)}{(u-6)(u+5)}. \] This simplifies to: \[ \frac{-11u - 8u - 40}{(u-6)(u+5)} = \frac{u^2 - 6u}{(u-6)(u+5)}. \] Combine the left side: \[ \frac{-19u - 40}{(u-6)(u+5)} = \frac{u^2 - 6u}{(u-6)(u+5)}. \] Since both sides have the same denominator, we can set the numerators equal: \[ -19u - 40 = u^2 - 6u. \] Rearranging gives: \[ u^2 + 13u + 40 = 0. \] Next, we factor the quadratic: \[ (u + 8)(u + 5) = 0. \] This gives us the solutions: \[ u + 8 = 0 \quad \Rightarrow \quad u = -8, \] \[ u + 5 = 0 \quad \Rightarrow \quad u = -5. \] We need to check for any restrictions from denominators. The values \( u = 6 \) and \( u = -5 \) would make the denominators zero. Thus, we exclude \( u = -5 \). Therefore, the valid solution is: \[ u = -8. \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy